An overview of sulfonamide-based conjugates: Recent advances for tuberculosis treatment - Scarim, Cauê Benito; Pavan, Fernando Rogério [UNESP] (Wiley, 2022)
In 2019, tuberculosis (TB) caused approximately 1.4 million deaths around the world. TB is an infectious respiratory disease mainly caused by Mycobacterium tuberculosis. The lack of new drugs to treat drug-resistant strains is a principal factor for the continuous slow rise in TB infections. Sulfonamides are active moieties in various drugs used against several sicknesses, including TB. Our aim is to aid the development of new TB treatments and drugs by describing recent improvements (2011–2021) to sulfonamide-based compounds.